Impact of user parameters in inversion velocity analysis. (23rd February 2020) - Zhou, T.; Chauris, H.; Audebert, F.
ABSTRACT: Migration velocity analysis is a method devoted to the evaluation of both reflectivity and background velocity models, associated with the high and low wavenumber components of the model, respectively. Inversion velocity analysis is one of its improved versions, leading to more stable background velocity updates. Still, the impact of the user parameters should be understood for an optimal update of the background velocity. We show that a sign reversal of the background velocity gradient could occur when the selected surface offset range or the space lag range is too small. We derive the theoretical limits and check their consistency through simulations in a simple model with a single interface. These guidelines determine the necessary ranges of surface offsets and space lags for a proper update of the background velocity model. We discuss their applicability on the Marmousi model. Artefacts in the retrieved background velocity model are observed when the guidelines are not satisfied.